Mapping and valuing urban ecosystem services in the greater Kuala Lumpur metropolitan city - Lourdes, Karen Thivya (2023)
Unprecedented urban growth has placed increasing pressure on cities globally. The intensive land use changes that follow urban growth often result in the degradation of natural ecosystems, with adverse consequences for the wellbeing of urban populations as the potential delivery of ecosystem services diminishes. This thesis: 1) investigated the spatial distribution of urban ecosystem services in Greater Kuala Lumpur, Malaysia, 2) tested the utilisation of two off-the-shelf ecosystem service valuation tools (SolVES and InVEST) in supporting urban planning, and 3) investigated the extent to which urban ecosystem services and urban biodiversity have been considered as part of sustainable development planning in Kuala Lumpur.